Actividades lúdicas para desarrollar la noción de clasificación - Juarez Vilcherrez, Renee (2021)
The present learning demonstration session "Playful activities to develop the notion of classification in 5-year-old children" of the Initial Level of Regular Basic Education has the purpose of learning the development of competence Solve problems of quantity "where skills are combined astranslated quantitiesto numerical expressions, communicates understanding of numbers and operations, uses estimation and calculation strategies and procedures. It also responds to performance. It establishes relationships between the objects in its environment according to their perceptual characteristics by comparing, grouping those similar objects that serve some purpose, and leaving some elements loose ", where children must group various materials according to color, shape or size, verbalizing the criteriaused. Faced with this sufficiency work, a socio-constructive position is assumed within the framework of the competency curriculum, being configured within the framework of the area of Mathematics in accordance with the problem-solving approach, and is oriented under the formative evaluation, within the intercultural humanist educational paradigm that promotes the Peruvian state.